Application of Five Formula Fertilizer N Slow Release on Growth and Results of Green Mustard Plant (Brassica juncea L.) - Fahmi, Muhammad (Jurnal Indonesia Sosial Sains, 2026)
The research aims to: (1) Determine the correct slow release N fertilizer formula to obtain maximum growth and yield of mustard greens; (2) Determine the amount of green mustard fertilizer in each formula of N slow release fertilizer. The design used in this study was a Complete Randomized Block Design (RCBD) with 1 factor, namely 5 levels of N slow release fertilizer and 1 control, namely F0 (N fertilizer formula as recommended); F1 (formula N fertilizer with a dose of 1.05 g / tan); F2 (formula fertilizer N at a dose of 0.74 g / tan); F3 (formula N fertilizer with a dose of 0.87 g / tan); F4 (formula fertilizer N at a dose of 0.72 g / tan); F5 (N fertilizer formula with a dose of 0.76 g / tan). The results showed the formula of slow-release N fertilizer caused differences in plant height, leaf area, and N uptake of plants with the highest absorption in formula F5 (slow-release N fertilizer with a composition of 7 urea: 2 Azolla microphylla: 1 montmorillonite) of 1.35%. Related and highest green mustard yield in F1 (slow-release N fertilizer with composition of 6 urea: 1 Azolla microphylla: 1 montmorillonite: 1 gum rosses: 1 humic acid) of 361.08 g / plant.